Works councils - sand or grease in the operation of German firms? - Schank, Thorsten; Schnabel, Claus; Wagner, Joachim (Applied Economics Letters, 2004)
Using a large panel data set it is investigated whether works councils act as sand or grease in the operation of German firms. Stochastic production frontier analysis indicates that establishments with and without a works council do not exhibit significant differences in efficienc
UnivIS-Import:2015-03-09:Pub.2004.rw.fbwiwi.worksc